Dynamic Downscaling in Climatology: A Review - Wahbeh, Alaa (Revista Brasileira de Geografia Física, 2025)
The paper discusses the significance of dynamic downscaling in climate modeling and its impact on regional climate predictions and adaptation strategies. Dynamic downscaling bridges the gap between coarse-resolution global climate models (GCMs) and the fine-scale climate information required for local decision-making and policy planning. It emphasizes the need for high-resolution data to accurately predict localized climate phenomena such as urban heat islands and extreme weather events. The study highlights various applications of dynamic downscaling, including urban planning, disaster preparedness, and hydrological impact studies. It discusses recent advances in the field, such as the integration of machine learning and artificial intelligence techniques, which enhance the precision and efficiency of climate models. These advancements are crucial for developing effective adaptation and mitigation strategies to address the impacts of climate change on urban environments and infrastructure. Furthermore, the paper underscores the importance of interdisciplinary approaches in improving model applicability and relevance. Integrating dynamic downscaling with other scientific disciplines enhances the accuracy of climate predictions and supports the development of robust adaptation plans. The paper also explores the challenges associated with computational demand and the need for continuous improvement in model resolution and accuracy to meet the expanding requirements of climate research and policy-making. In conclusion, dynamic downscaling is a vital tool for translating global climate projections into actionable local climate information, thereby supporting effective climate change adaptation and mitigation efforts.